Targeted controlled-release drug delivery system based on polymer nano-carrier and preparation method of targeted controlled-release drug delivery system
By constructing a three-layer polymer nanocarrier system, combined with targeting aptamers and microenvironment-responsive peptides, the challenges of insufficient drug loading and release rate control in drug delivery systems for tumor treatment were solved. This enabled precise drug release and stable delivery to the tumor site, improving therapeutic efficacy and reducing toxicity.
Patent Information
- Application Number
- CN202511810505.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-03
- Publication Date
- 2026-01-02
AI Technical Summary
Existing polymer nanoparticle systems suffer from limitations in drug delivery, including limited drug loading capacity, difficulty in precisely controlling release rate, low targeting efficiency, and insufficient stability in complex pathological microenvironments. In particular, they lack multi-layered synergistic mechanisms and have poor response specificity in tumor treatment.
A three-layer structure based on polymer nanocarriers, including a core layer, a shell layer, and an outer shell layer, was constructed. Combined with tumor membrane targeting aptamers and microenvironment-responsive peptides, the precise identification and controlled release of drugs at tumor sites were achieved.
It improves the ability of drugs to accumulate and release in a controlled manner at the lesion site, enhances the therapeutic effect and reduces systemic toxicity, and demonstrates high efficiency and stability in a simulated tumor microenvironment.
Smart Images

Figure CN121243424A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of biomedical materials and targeted drug delivery systems, and particularly relates to a targeted controlled-release drug delivery system based on a polymer nanocarrier and a preparation method thereof. BACKGROUND
[0002] At present, the nanodrug delivery system shows wide application prospects in the fields of antitumor drug delivery, biological therapy and targeted release. Among them, the polymer nanocarrier is widely used to construct an intelligent drug release platform due to its good biocompatibility, controllable release and structural adjustability. However, the existing polymer nanoparticle system generally has the problems of limited drug loading capacity, difficult accurate control of release rate, low targeting efficiency and insufficient stability in complex pathological microenvironments, which limits its further application in precision therapy. Especially in tumor treatment, the complexity of the lesion microenvironment (such as increased enzyme concentration and decreased pH) puts higher requirements on the drug delivery system. At present, some studies have tried to construct responsive materials or introduce targeting ligands to improve the therapeutic effect, but most of the systems have a single structure, lack of multi-layer structure synergy mechanism, and the targeting mechanism also depends on single molecular recognition, the release process has poor response specificity, and non-targeted release and systemic toxicity are easy to occur.
[0003] Therefore, there is an urgent need for a polymer nanodrug delivery system with clear structural hierarchy, multiple targeting ability and response to tumor microenvironment, to improve the precision aggregation and controllable release of drugs at the lesion site, thereby enhancing the therapeutic effect and reducing systemic toxicity. SUMMARY
[0004] To solve the problems mentioned in the background, the purpose of the present application is to provide a targeted controlled-release drug delivery system based on a polymer nanocarrier and a preparation method thereof, to construct a core-shell-shell three-layer structure, to combine a targeting aptamer and a microenvironment responsive peptide, to realize the precise recognition and controlled release of drugs at the tumor site, and to improve the therapeutic efficiency and reduce the toxicity.
[0005] The purpose of the present application can be achieved by the following technical solutions:
[0006] A targeted controlled-release drug delivery system based on a polymer nanocarrier comprises the following raw materials by weight: polyvinyl alcohol 100-150 parts, active pharmaceutical ingredient 10-30 parts, polylactic acid-glycolic acid copolymer 50-100 parts, polyvinyl alcohol-aldehyde dextran graft copolymer 30-80 parts, tumor membrane targeting aptamer 0.5-3 parts, and microenvironment responsive peptide 0.5-3 parts.
[0007] The polyvinyl alcohol forms a core layer, the polylactic acid-glycolic acid copolymer forms a shell layer, the polyvinyl alcohol-aldehyde dextran graft copolymer forms an outer shell layer, and the tumor membrane targeting aptamer is covalently modified with a microenvironment responsive peptide on the surface of the outer shell layer.
[0008] Further preferably, the preparation method of the polylactic acid-glycolic acid copolymer specifically comprises the following steps:
[0009] S101. L-lactic acid and glycolic acid monomers are added to a reaction kettle, nitrogen is introduced for replacement, stannous octoate is added, and uniform mixing is performed under stirring;
[0010] S102. The reaction kettle is sealed, the reaction system is heated, and after the reaction is completed, natural cooling is performed;
[0011] S103. The reaction product is taken out, and dissolution, precipitation, filtration and drying are sequentially performed to obtain the polylactic acid-glycolic acid copolymer.
[0012] Further preferably, the preparation method of the polyvinyl alcohol-aldehyde dextran graft copolymer specifically comprises the following steps:
[0013] S201. Dextran is dissolved in water, sodium meta-periodate is added, and reaction is performed under light shielding conditions, after which impurities are removed and dried to obtain aldehyde dextran;
[0014] S202. Polyvinyl alcohol is added to water, heated and stirred to dissolve, and cooled for standby, and a uniform solution is prepared;
[0015] S203. Aldehyde dextran is added to the polyvinyl alcohol solution, the pH condition is adjusted, and reaction is performed under stirring, after which impurities are removed and dried to obtain the polyvinyl alcohol-aldehyde dextran graft copolymer.
[0016] Further preferably, the tumor membrane targeting aptamer is a single-stranded DNA or RNA aptamer, which is coupled to the surface of the outer shell layer through an EDC / NHS reaction, and has the ability to recognize tumor cell membrane receptors.
[0017] Further preferably, the microenvironment responsive peptide is a functional polypeptide capable of specifically binding to metal matrix protease MMP-2, which is grafted to the outer shell layer polymer segment through an amine-carboxyl condensation reaction.
[0018] Further preferably, the crosslinking density between the core layer and the shell layer is 2-6 mol%, and the crosslinking density between the shell layer and the outer shell layer is 0.5-2 mol%, forming a three-layer stable coating structure.
[0019] A preparation method of a targeted controlled-release drug delivery system based on a polymer nanocarrier, comprising the following steps:
[0020] S1. Add polyvinyl alcohol and a pharmaceutically active ingredient into deionized water, stir and mix uniformly, freeze and stand, then thaw, repeat the freezing-thawing operation, and form a core layer structure;
[0021] S2. Add polylactic acid-glycolic acid copolymer into ethyl acetate, form an emulsion with the core layer structure, then evaporate the ethyl acetate, and obtain a shell layer structure;
[0022] S3. Dissolve polyvinyl alcohol-aldehyde dextran graft copolymer in water, add the shell layer structure particles, stir and mix, and form an outer shell layer structure;
[0023] S4. Disperse the outer shell layer structure in a buffer solution, sequentially add EDC and NHS, stir and activate, then add tumor membrane targeting aptamer and microenvironment responsive peptide, and obtain the drug delivery system.
[0024] Further preferably, in step S1, the concentration of the polyvinyl alcohol is 8-12%, the freezing temperature is-20℃, and the freezing frequency is 2-4 times.
[0025] Further preferably, in step S3, the outer shell layer material is crosslinked at pH 5.0-6.0 for 2-4 hours to form a responsive structure containing an acetal bond.
[0026] Further preferably, in step S4, the mass ratio of the tumor membrane targeting aptamer to the microenvironment responsive peptide is 1:1, the coupling reaction time is 3-6 hours, and the reaction pH is 6.8-7.2.
[0027] The present application has the following beneficial effects:
[0028] The present application realizes the function integration of high drug loading, good biocompatibility and controllable release by designing a three-layer synergistic structure, i.e., a core layer, a shell layer and an outer shell layer. The core layer is mainly polyvinyl alcohol, which has good water solubility and drug loading capacity; the middle shell layer adopts poly (lactic-co-glycolic acid), which provides structural support and biodegradation performance; and the outer shell layer is composed of polyvinyl alcohol-aldehyde dextran graft copolymer, which not only improves the stability and dispersibility of the particles, but also provides functional sites for subsequent grafting of targeting ligands. By further grafting tumor membrane targeting aptamers and microenvironment responsive peptides on the surface of the particles, double-ligand synergistic targeting is realized, which can specifically recognize the tumor cell surface and respond to the enzyme or pH condition of the lesion area to trigger drug release, effectively improving the local utilization rate of the drug and the treatment effect. Through in vitro release experiments, it is verified that the system shows a much higher release rate under the simulated tumor microenvironment condition (pH 6.5 + MMP-2) than under the neutral condition, and the response is clear and controllable; particle size testing also shows that the three-layer structure has excellent structural stability, with small particle size change, low PDI and stable Zeta potential within 48 hours, which is much better than the comparative sample; the targeting recognition experiment further shows that the uptake amount of the nanoparticles of the embodiment in tumor cells is much higher than that of the control group without grafting or with incomplete structure, verifying the effectiveness of the double-ligand synergistic targeting strategy. BRIEF DESCRIPTION OF DRAWINGS
[0029] The present application will be further described below in conjunction with the drawings.
[0030] Figure 1 Cumulative release rate curve diagram of the samples of examples 1-3 and comparative examples 1-2 in vitro at pH 7.4;
[0031] Figure 2 Cumulative release rate curve diagram of the samples of examples 1-3 and comparative examples 1-2 in vitro under the condition of pH 6.5 + MMP-2;
[0032] Figure 3 Fluorescence intensity comparison column chart of the samples of examples 1-3 and comparative examples 1-2 in HeLa cells. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings of the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0034] Example 1
[0035] I. Preparation of poly (lactic-co-glycolic acid)
[0036] 33.75 g L-lactic acid and 11.25 g glycolic acid monomers were weighed out and mixed, and then added to a reaction kettle. Nitrogen was introduced to replace oxygen at room temperature for 30 minutes, and then 0.2 g stannous octoate was added under nitrogen protection, and stirred and mixed uniformly. The reaction kettle was closed, and vacuum melt polycondensation reaction was carried out at 180°C. The reaction temperature was maintained for 12 hours, and the reaction pressure was controlled to be not higher than 100 Pa. After the reaction was completed, the reaction was naturally cooled to room temperature. The reaction was taken out, dissolved in 200 mL chloroform, slowly added into 600 mL pre-cooled ethanol to precipitate the product, and then subjected to suction filtration after standing. The obtained precipitate was washed with ethanol for 2 times, and vacuum dried at 40°C for 24 hours to obtain the lactic acid-glycolic acid copolymer.
[0037] II. Preparation of polyvinyl alcohol-aldehyde dextran graft copolymer
[0038] 2.0 g of dextran was dissolved in 50 mL of deionized water, stirred until clear and transparent, and 0.428 g of sodium metaiodate was slowly added at room temperature and in the dark. The stirring reaction was continued for 4 hours. After the reaction was completed, the dialysis bag was used to dialyze in deionized water for 48 hours, and the water was changed every 6 hours. The dialysate was freeze-dried to obtain light yellow powder of aldehyde dextran. 4.0 g of polyvinyl alcohol was added to 50 mL of deionized water, and stirred at 80°C water bath for 1 hour until completely dissolved. The solution was cooled to room temperature to obtain a 4 wt% polyvinyl alcohol uniform solution. The aldehyde dextran was slowly added to the polyvinyl alcohol solution, and the pH of the system was adjusted to 4.5-5.0. The magnetic stirring reaction was carried out at room temperature for 24 hours. After the reaction was completed, the system was added into 200 mL of cold ethanol to precipitate the product. After standing for 30 minutes, suction filtration was carried out. The filter cake was washed with ethanol for 2 times, and then placed in a vacuum dryer at 40°C for 24 hours to obtain the polyvinyl alcohol-aldehyde dextran graft copolymer.
[0039] III. Preparation of drug delivery system
[0040] The drug delivery system comprises the following raw materials by weight: polyvinyl alcohol 100 parts, active pharmaceutical ingredient 10 parts, polylactic acid-glycolic acid copolymer 50 parts, polyvinyl alcohol-aldehyde dextran graft copolymer 30 parts, tumor membrane targeting aptamer 0.5 parts, and microenvironment responsive peptide 0.5 parts.
[0041] The polyvinyl alcohol forms a core layer, the polylactic acid-glycolic acid copolymer forms a shell layer, the polyvinyl alcohol-aldehyde dextran graft copolymer forms an outer shell layer, and the tumor membrane targeting aptamer and the microenvironment responsive peptide are covalently modified on the surface of the outer shell layer.
[0042] The preparation steps of the above drug delivery system are as follows:
[0043] S1. Take 100 g of polyvinyl alcohol and 10 g of doxorubicin hydrochloride and add them to 1000 mL of deionized water, stir under 80°C water bath for 1 hour until completely dissolved, cool to room temperature, then pour the solution into a mold, freeze at -20°C for 12 hours, then thaw, repeat the freezing-thawing operation 3 times, take out the formed polyvinyl alcohol-drug gel, use a high-shear homogenizer to disperse to form nanoscale core gel particles, and reserve for use.
[0044] S2. Take 50 g of polylactic acid-glycolic acid copolymer and dissolve it in 200 mL of ethyl acetate, stir to form an oil phase solution, disperse the above core particles in 200 mL of deionized water containing 1% Tween 80, slowly add the oil phase to the water phase, use ultrasonic emulsification treatment (power 300W, time 5min), form O / W emulsion, then naturally volatilize ethyl acetate at room temperature, centrifugal recovery of precipitate, water washing to obtain core-shell structure nanoparticles coated with shell layer.
[0045] S3. Take 30 g of polyvinyl alcohol-alded dextran graft copolymer and dissolve it in 300 mL of deionized water, adjust the pH of the solution to 5.2, add the above obtained core-shell nanoparticles to the solution, stir at room temperature for 3 hours, then collect the particles by membrane filtration, wash with deionized water 3 times, and reserve for use.
[0046] S4. Disperse the outer shell layer nanoparticles in 100 mL of 0.05 mol / L MES buffer (pH 6.8), add 20 mg of 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) and 12 mg of N-hydroxysuccinimide (NHS), stir at room temperature for 30 minutes, then add 0.5 g of tumor membrane targeting aptamer and 0.5 g of microenvironment responsive peptide, continue to react for 4 hours, after the reaction is completed, centrifugal collection of product, with deionized water washing 3 times, to obtain the targeted controlled release nanodrug delivery system.
[0047] Example 2
[0048] The preparation method of the polylactic acid-glycolic acid copolymer and the polyvinyl alcohol-alded dextran graft copolymer is the same as that of Example 1.
[0049] The drug delivery system comprises the following raw materials by weight: polyvinyl alcohol 150 parts, active pharmaceutical ingredient 30 parts, polylactic acid-glycolic acid copolymer 100 parts, polyvinyl alcohol-alded dextran graft copolymer 80 parts, tumor membrane targeting aptamer 3 parts, microenvironment responsive peptide 3 parts;
[0050] Among them, the polyvinyl alcohol forms the core layer, the polylactic acid-glycolic acid copolymer forms the shell layer, the polyvinyl alcohol-alded dextran graft copolymer forms the outer shell layer, and the tumor membrane targeting aptamer and the microenvironment responsive peptide are covalently modified on the surface of the outer shell layer.
[0051] The preparation steps of the above drug delivery system are as follows:
[0052] S1. Take 150 g of polyvinyl alcohol and 30 g of doxorubicin hydrochloride and add them to 1500 mL of deionized water, and place them in a water bath at 80°C for heating and stirring for 1 hour until completely dissolved. After cooling to room temperature, place them in a freezer at -20°C for 12 hours, and after thawing, repeat the freezing-thawing cycle 4 times. Take out the formed gel and process it using a high-speed homogenizer to obtain polyvinyl alcohol-drug nanogel particles with uniform particle size.
[0053] S2. Take 100 g of polylactic acid-glycolic acid copolymer and dissolve it in 400 mL of ethyl acetate as an oil phase, and stir it uniformly, and disperse the gel particles in 400 mL of deionized water containing 1% Tween 80 as an aqueous phase, and slowly add the oil phase to the aqueous phase using a constant-speed dropping method, and process it using an ultrasonic emulsification device (power 400 W, time 8 minutes). Place it at room temperature for 4 hours to allow the ethyl acetate to volatilize naturally, and wash it with deionized water 3 times and reserve it for use.
[0054] S3. Take 80 g of polyvinyl alcohol-alded dextran graft copolymer and add it to 400 mL of deionized water and stir to dissolve it, and adjust the pH to 5.0. Add the above core-shell structure particles to the solution and stir for 4 hours. After the reaction is completed, filter it using a 0.45 μm microporous filter membrane, collect the three-layer structure particles with the outer shell coated, and wash them with water and reserve them for use.
[0055] S4. Disperse the three-layer structure nanoparticles in 150 mL of 0.05 mol / L MES buffer (pH 6.8), add 40 mg of EDC and 24 mg of NHS, and stir at room temperature for 30 minutes. Then add 3 g of tumor membrane targeting aptamer and 3 g of microenvironment responsive peptide, and continue to react in the buffer for 6 hours. Collect it by centrifugation and wash it with deionized water 3 times, and freeze-dry it to obtain the targeted controlled-release drug delivery nanosystem.
[0056] Example 3
[0057] The preparation method of the polylactic acid-glycolic acid copolymer and the polyvinyl alcohol-alded dextran graft copolymer is the same as that of Example 1.
[0058] The drug delivery system contains the following raw materials by weight: polyvinyl alcohol 125 parts, active pharmaceutical ingredient 20 parts, polylactic acid-glycolic acid copolymer 75 parts, polyvinyl alcohol-alded dextran graft copolymer 55 parts, tumor membrane targeting aptamer 1.5 parts, and microenvironment responsive peptide 1.5 parts.
[0059] The polyvinyl alcohol forms a core layer, the polylactic acid-glycolic acid copolymer forms a shell layer, the polyvinyl alcohol-aldehyde dextran graft copolymer forms an outer shell layer, and the tumor membrane targeting aptamer and the microenvironment responsive peptide are covalently modified to the surface of the outer shell layer.
[0060] The preparation steps of the above drug delivery system are as follows:
[0061] S1. 125 g of polyvinyl alcohol and 20 g of doxorubicin hydrochloride are weighed and added to 1200 mL of deionized water, and placed in a water bath at 80°C for heating and stirring for 1 hour to completely dissolve. After the solution is cooled to room temperature, it is divided into molds, frozen at -20°C for 12 hours, and then thawed; the freezing-thawing cycle is repeated 3 times. The formed polyvinyl alcohol-drug gel is treated with a high-speed homogenizer to obtain core nanogel particles with uniform particle size.
[0062] S2. 75 g of polylactic acid-glycolic acid copolymer is dissolved in 300 mL of ethyl acetate as an oil phase; the gel particles are dispersed in 300 mL of deionized water containing 1% Tween 80. After the oil phase is slowly added to the water phase, an ultrasonic emulsification device (power 350 W, time 6 minutes) is used for treatment. The emulsion is placed at room temperature for about 3 hours to allow the ethyl acetate to volatilize, and then the particles are collected by centrifugation and washed with deionized water 3 times to obtain core-shell nanoparticles coated with a shell layer.
[0063] S3. 55 g of polyvinyl alcohol-aldehyde dextran graft copolymer is weighed and added to 350 mL of deionized water, stirred to dissolve, and the pH of the system is adjusted to 5.1. The core-shell structure nanoparticles are added to the above solution, and magnetic stirring is carried out at room temperature for 3 hours. After the reaction is completed, 0.45 μm filter membrane is used for filtration and washing with deionized water 2 times to obtain the outer shell layer coated three-layer structure particles.
[0064] S4. The three-layer structure nanoparticles are dispersed in 120 mL of 0.05 mol / L MES buffer, 30 mg of EDC and 18 mg of NHS are added, and stirred at room temperature for 30 minutes. Then 1.5 g of tumor membrane targeting aptamer and 1.5 g of microenvironment responsive peptide are added, and the reaction is continued in the buffer for 5 hours. Centrifugation and washing 3 times, freeze-drying, to obtain the targeted controlled-release drug delivery nanosystem.
[0065] Comparative Example 1
[0066] The preparation method of the polylactic acid-glycolic acid copolymer and the polyvinyl alcohol-aldehyde dextran graft copolymer is the same as that of Example 1.
[0067] The drug delivery system comprises the following raw materials by weight: 125 parts of polyvinyl alcohol, 20 parts of a drug active ingredient, 75 parts of polylactic acid-glycolic acid copolymer, 55 parts of polyvinyl alcohol-aldehyde dextran graft copolymer, 1.5 parts of tumor membrane targeting aptamer;
[0068] The polyvinyl alcohol forms a core layer, the polylactic acid-glycolic acid copolymer forms a shell layer, the polyvinyl alcohol-aldehyde dextran graft copolymer forms an outer shell layer, and the tumor membrane targeting aptamer is modified on the surface of the outer shell layer.
[0069] The preparation steps of the drug delivery system are the same as those in Example 3, except that no microenvironment responsive peptide is added in step S4.
[0070] Comparative Example 2
[0071] The polylactic acid-glycolic acid copolymer is prepared by the same method as in Example 1.
[0072] The drug delivery system comprises the following raw materials by weight: 125 parts of polyvinyl alcohol, 20 parts of a drug active ingredient, 75 parts of polylactic acid-glycolic acid copolymer, 1.5 parts of tumor membrane targeting aptamer, and 1.5 parts of microenvironment responsive peptide;
[0073] The preparation steps of the drug delivery system are the same as those in Example 3, except that no polyvinyl alcohol-aldehyde dextran graft copolymer is added in step S3.
[0074] Performance test
[0075] 1. In vitro drug release test
[0076] The nanocarriers obtained in Examples 1-3 and Comparative Examples 1-2 were respectively placed in dialysis bags with a molecular weight cutoff of 8 kDa, and 5 mL of a nanometer particle solution containing an equal amount of drug was added to each bag. The dialysis bags were then placed in 50 mL of different release media, including PBS buffer at pH 7.4 (simulating normal tissue environment) and buffer at pH 6.5 with the addition of 50 ng / mL metal matrix protease MMP-2 (simulating tumor acidic microenvironment). The experiment was carried out at 37°C with 100 rpm shaking. 1 mL was taken at 1, 4, 12, 24, and 48 hours, and an equal amount of fresh medium was added. The sample was filtered through a 0.22 µm filter membrane, and the drug concentration was determined using HPLC to calculate the cumulative release amount, as shown in Tables 1 and 2 below.
[0077] Table 1 Cumulative release rate (%) in vitro at pH 7.4
[0078] Time (h) Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 4 18 16 17 22 35 12 28 25 26 38 55 24 36 33 34 52 72 48 45 42 43 65 88
[0079] Table 2 Cumulative release rate (%) in vitro at pH 6.5 + MMP-2
[0080] Time (h) Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 4 32 35 34 25 48 12 55 58 56 40 70 24 71 75 73 52 88 48 88 92 90 66 100
[0081] As can be seen from Table 1 and Table 2, the nano delivery system of the present application exhibits excellent performance in structural design and functional response. Examples 1-3 all adopt a three-layer structure construction scheme, and introduce tumor membrane targeting aptamer and microenvironment responsive peptide as surface functional ligands. In the pH 6.5 and MMP-2 environment, the 24 h cumulative release rate of the three groups of examples all reaches more than 70%, which is significantly higher than the release rate in the pH 7.4 environment, indicating that the system can realize rapid responsive release in the lesion microenvironment. In contrast, Comparative Example 1 removes the microenvironment responsive peptide and only relies on aptamer modification, resulting in a smaller release increase under acidic + enzyme conditions, indicating the key role of the responsive peptide in triggering drug release. Comparative Example 2 does not set the shell layer structure, although the initial release amount is high, but the release process lacks regulation, and it is completely released at 48 h, showing poor structural stability and weak controlled release ability.
[0082] 2. Target recognition ability test
[0083] The nano delivery systems prepared in Examples 1-3 and Comparative Examples 1-2 were labeled with DiI fluorescent dye, and after incubation in the dark for 30 minutes, the free dye was removed and centrifuged and washed 3 times. The labeled nanoparticles were incubated with human cervical cancer HeLa cells at the same concentration (equivalent to a drug concentration of 5 μg / mL), and the incubation concentration was 1×10 6 cells / well, and incubated in a 37°C incubator for 4 hours. After incubation, the nanoparticles that were not taken up were removed, washed 3 times with PBS, the cells were fixed, and the red fluorescence intensity was observed using a confocal laser scanning microscope to reflect the nanoparticle uptake efficiency. The images were analyzed by ImageJ, and the average gray value of fluorescence was extracted as the quantitative result, as shown in Table 3 below.
[0084] Table 3 Fluorescence intensity of nanoparticles in HeLa cells
[0085] Sample Fluorescence intensity (AU) Example 1 125 Example 2 142 Example 3 134 Comparative Example 1 87 Comparative Example 2 60
[0086] As can be seen from Table 3, the nanoparticles of Examples 1-3 all exhibit high red fluorescence intensity in HeLa cells, indicating that the cell uptake efficiency is significantly improved, among which Example 2 is the highest, reaching 142 AU, indicating that the targeting recognition effect is the strongest when the double-ligand modification amount is higher. By covalently grafting tumor membrane targeting aptamers and microenvironment responsive peptides on the surface of the nanoparticle shell, the present application realizes the synergistic effect of cell membrane receptor recognition and tumor enzyme response, so that the nanoparticle has higher enrichment capacity and intracellular uptake efficiency in the lesion tissue. Comparative Example 1 lacks a responsive peptide, resulting in the absence of a local enzyme triggering mechanism, and the fluorescence intensity decreases to 87 AU, while Comparative Example 2 lacks a shell layer, has an incomplete structure, and has low ligand grafting efficiency, only 60 AU.
[0087] 3. Nanoparticle size and structural stability test
[0088] The nanoparticles prepared in Examples 1-3 and Comparative Examples 1-2 were dispersed in pH 7.4 PBS buffer and pH 6.5 weak acid buffer at a concentration of 1 mg / mL, and sampled after standing at 37°C for 0, 24, and 48 hours, respectively. The average particle size, PDI (polydispersity index), and Zeta potential were measured using a dynamic light scattering instrument (DLS) to evaluate the structural stability and dispersion performance of the nanoparticles. The results are shown in Table 4 below.
[0089] Table 4 Particle size and structural stability results after 48 hours
[0090] Sample Initial particle size (nm) 48 h particle size (nm) PDI (48 h) Zeta potential (mV) Example 1 165 172 0.18 −21.3 Example 2 180 186 0.16 −22.7 Example 3 174 179 0.17 −21.9 Comparative Example 1 168 185 0.28 −17.5 Comparative Example 2 170 245 0.41 −9.2
[0091] As can be seen from Table 4, the particle size change of Examples 1-3 after 48 hours at 37°C is less than 10 nm, the PDI is maintained at 0.16-0.18, and the absolute value of Zeta potential is about -21 mV, indicating that the three-layer polymer nanoparticle delivery system constructed by the present application has good structural stability and dispersion. The key lies in that the shell layer is composed of polyvinyl alcohol-alded dextran graft copolymer, which has moderate crosslinking strength and water affinity, can effectively coat the shell layer and inhibit particle aggregation, and maintain particle size uniformity and colloidal stability. Although Comparative Example 1 retains the shell layer, the absence of the microenvironment responsive peptide leads to uneven surface charge distribution, the PDI rises to 0.28, and the stability decreases. Comparative Example 2 does not contain a shell layer, the absolute value of Zeta potential significantly decreases to -9.2 mV, the PDI is as high as 0.41, and the particle size significantly swells to 245 nm, showing obvious aggregation.
[0092] In the description of the specification, the description of the terms "one embodiment", "an example", "a specific example" and the like means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In the specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Also, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0093] The basic principles, main features and advantages of the present application are shown and described above. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and descriptions in the specification are only to illustrate the principles of the present application. Without departing from the spirit and scope of the present application, various changes and improvements can be made to the present application, and these changes and improvements all fall within the scope of the claimed present application.
Claims
1. A polymer nanocarrier based targeted controlled release drug delivery system, characterized in that, The drug delivery system comprises the following raw materials by weight: 100-150 parts of polyvinyl alcohol, 10-30 parts of a pharmaceutically active ingredient, 50-100 parts of polylactic acid-glycolic acid copolymer, 30-80 parts of polyvinyl alcohol-aldehyde dextran graft copolymer, 0.5-3 parts of tumor membrane targeting aptamer, and 0.5-3 parts of microenvironment responsive peptide. The polyvinyl alcohol forms a core layer, the polylactic acid-glycolic acid copolymer forms a shell layer, and the polyvinyl alcohol-aldehyde dextran graft copolymer forms an outer shell layer.
2. The drug delivery system of claim 1, wherein, The preparation method of the polylactic acid-glycolic acid copolymer specifically comprises the following steps: S101. L-lactic acid and glycolic acid monomers are added to a reaction kettle, nitrogen is introduced for replacement, stannous octoate is added, and stirring is performed under the condition of mixing uniformly; S102. The reaction kettle is sealed, the reaction system is heated, and after the reaction is completed, natural cooling is performed; S103. The reaction product is taken out, and is sequentially subjected to dissolution, precipitation, filtration, and drying to obtain the polylactic acid-glycolic acid copolymer.
3. The drug delivery system of claim 1, wherein, The preparation method of the polyvinyl alcohol-aldehyde dextran graft copolymer specifically comprises the following steps: S201. Dextran is dissolved in water, sodium meta-periodate is added, and reaction is performed under the condition of avoiding light, impurities are removed after the reaction is completed, and drying is performed to obtain aldehyde dextran; S202. Polyvinyl alcohol is added to water, is dissolved by heating and stirring, and is cooled for standby, and a uniform solution is prepared; S203. Aldehyde dextran is added to the polyvinyl alcohol solution, the pH condition is adjusted, and reaction is performed under the condition of stirring, and after the reaction is completed, impurities are removed and dried to obtain the polyvinyl alcohol-aldehyde dextran graft copolymer.
4. The drug delivery system of claim 1, wherein, The tumor membrane targeting aptamer is a single-stranded DNA or RNA aptamer, is coupled to the surface of the outer shell layer through an EDC / NHS reaction, and has the ability to recognize tumor cell membrane receptors.
5. The drug delivery system of claim 1, wherein, The microenvironment responsive peptide is a functional polypeptide capable of specifically binding to metal matrix protease MMP-2, and is grafted to the outer shell layer polymer chain segment through an amine-carboxyl condensation reaction.
6. The drug delivery system of claim 1, wherein, The crosslinking density between the core layer and the shell layer is 2-6 mol%, and the crosslinking density between the shell layer and the outer shell layer is 0.5-2 mol%, forming a three-layer stable coating structure.
7. A method for preparing a polymer nanocarrier-based targeted controlled release drug delivery system as claimed in any one of claims 1 to 6, wherein the drug delivery system is prepared by the following steps of: (a) preparing a polymer nanocarrier; (b) loading the drug into the polymer nanocarrier; (c) modifying the surface of the polymer nanocarrier with a targeting ligand; and (d) encapsulating the drug delivery system in a biodegradable polymer. The preparation method comprises the following steps: S1. Polyvinyl alcohol and a pharmaceutically active ingredient are added to deionized water, are stirred and mixed uniformly, are frozen and placed after thawing, and the freezing-thawing operation is repeated to form a core layer structure; S2. Polylactic acid-glycolic acid copolymer is added to ethyl acetate, an emulsion is formed by adding the core layer structure, and then the ethyl acetate is evaporated to obtain a shell layer structure; S3. Polyvinyl alcohol-aldehyde dextran graft copolymer is dissolved in water, the shell layer structure particles are added, and stirring and mixing are performed to form an outer shell layer structure; S4. The outer shell layer structure is dispersed in a buffer solution, EDC and NHS are sequentially added, stirring is performed after activation, and tumor membrane targeting aptamer and microenvironment responsive peptide are added to obtain the drug delivery system.
8. The method of claim 7, wherein the drug delivery system is prepared by, In step S1, the concentration of the polyvinyl alcohol is 8-12%, the freezing temperature is-20℃, and the freezing frequency is 2-4 times.
9. The method of claim 7, wherein the drug delivery system is prepared by, The shell layer material in step S3 is crosslinked for 2-4 hours under the condition of pH 5.0-6.0 to form a response structure containing an acetal bond.
10. The method of claim 7, wherein the drug delivery system is prepared by, The mass ratio of the tumor membrane targeting aptamer to the microenvironment response peptide in step S4 is 1:1, the coupling reaction time is 3-6 hours, and the reaction pH is 6.8-7.2.